Comparative Analysis of Chloroplast Genomes of Dalbergia Species for Identification and Phylogenetic Analysis - Hoi-Yan Wu; Kwan-Ho Wong; Bobby Lim-Ho Kong; Tin-Yan Siu; Grace Wing-Chiu But; Stacey Shun-Kei Tsang; David Tai-Wai Lau; Pang-Chui Shaw (Plants, 2022)
Dalbergia L.f. is a pantropical genus consisting of 269 species of trees, shrubs, and woody lianas. This genus is listed in CITES Appendices because of illegal logging and trafficking driven by the high economic value of its heartwood. Some species are also used medicinally. Species identification of Dalbergia timber and herbs is challenging but essential for CITES implementation. Molecular methods had been developed for some timber species, mostly from Madagascar and Southeast Asia, but medicinal species in south China were usually not included in those studies. Here, we sequenced and assembled the chloroplast genomes of five Dalbergia species native to Hong Kong, four of which are medicinal plants. Our aim is to find potential genetic markers for the identification of medicinal Dalbergia species based on divergence hotspots detected in chloroplast genomes after comparative and phylogenetic analysis. Dalbergia chloroplast genomes displayed the typical quadripartite structure, with the 50 kb inversion found in most Papilionoideae lineages. Their sizes and gene content are well conserved. Phylogenetic tree of Dalbergia chloroplast genomes showed an overall topology similar to that of ITS sequences. Four divergence hotspots (trnL(UAA)-trnT(UGU), ndhG-ndhI, ycf1a and ycf1b) were identified and candidate markers for identification of several Dalbergia species were suggested.